One-pot synthesis of 5-hydroxymethylfurfural by cellulose hydrolysis over highly active bimodal micro/mesoporous H-ZSM-5 catalyst - Nandiwale, Kakasaheb Y.; Galande, Nitish D.; Thakur, Pratika; Sawant, Sanjay D.; Zambre, Vishal P.; Bokade, Vijay V. (ACS Sustainable Chemistry & Engineering, 2014)
Direct synthesis of 5-hydroxymethylfurfural (5-HMF), a useful renewable biofuel and biochemical, was systematically studied by hydrolysis of microcrystalline cellulose over Bimodal-HZ-5 zeolite. Bimodal-HZ-5 zeolite obtained by post-synthesis modification of H-ZSM-5 with desilication was found to be a potential heterogeneous catalyst with 67% cellulose conversion and 46% yield of 5-HMF. Bimodal-HZ-5 was observed to be reusable for four cycles, without any loss in activity. The detailed optimization of process parameters and catalyst reusability are also presented. The present study opens a new avenue for the renewable one-pot synthesis of 5-HMF, a valuable product.
Keywords: 5-Hydroxymethylfurfural; Biomodal-HZ-5; glucose; Hydrolysis; Microcrystalline cellulose

Benzylation of acetic acid to benzyl acetate over highly active and reusable micro/meso-HZSM-5 - Nandiwale, Kakasaheb Y.; Galande, Nitish D.; Raut, Sunil A.; Bokade, Vijay V. (Chemical Engineering Research & Design, 2015)
Catalytic benzylation of acetic acid (AA) with benzyl alcohol (BA) to benzyl acetate was studied over zeolites viz. H-ZSM-5 (microporous, medium pore), Micro/Meso-HZSM-5 (combination of micro- and meso pore), H-Beta (microporous, large pore) to investigate catalytic activity and selectivity towards benzyl acetate. Micro/Meso-HZSM-5 obtained by desilication post-treatment has been employed as a heterogeneous catalyst for benzylation reaction probably for the first time. Micro/Meso-HZSM-5 was found to be a promising catalyst for benzylation with AA conversion of 94%, selectivity towards benzyl acetate of 95%. The detailed optimization of process parameters such as molar ratio, catalyst loading, reaction temperature and time was also presented. Micro/Meso-HZSM-5 catalyst was observed to be stable for six cycles (1 fresh and 5 recycles). The first order reaction kinetics (R-2 >0.98) indicated that reaction rate constants increased with increasing reaction temperature. The activation energy for benzylation of AA with BA over Micro/Meso-HZSM-5 was obtained to be 15.07 kJ mol(-1), which is far less than the reported. (C) 2014 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Acetic acid; Benzyl acetate; Benzyl alcohol; Benzylation; Micro/Meso-HZSM-5; Reaction kinetics

Process optimization by response surface methodology for transesterification of renewable ethyl acetate to butyl acetate biofuel additive over borated USY zeolite - Nandiwale, Kakasaheb Y.; Galande, Nitish D.; Bokade, Vijay V. (RSC Advances, 2015)
Butyl acetate, a renewable biofuel additive was synthesized by transesterification of butanol with ethyl acetate via a renewable and sustainable route. Use of fermentation derived bio-butanol and bio-ethyl acetate for synthesis of butyl acetate would be a more advantageous route over conventional Fischer Esterification. For the first time, a heterogeneous zeolite catalyst such as Ultra Stable Y (USY) and its modified versions obtained by borating on parent USY were used for the synthesis of butyl acetate. Response surface methodology (RSM) was employed to optimize the process parameters for transesterification of butanol with ethyl acetate over a 4% (w/w) B-USY catalyst. The influence of three crucial process variables such as catalyst loading, molar ratio, and reaction temperature on yield of butyl acetate were addressed by Box-Behnken experimental design (BBD). 4% (w/w) B-USY was proved to be a potential catalyst with 96% yield of butyl acetate at optimum process parameters. The 4% (w/w) B-USY catalyst was found to be reusable for 6 catalytic cycles.